Growth, body composition, ammonia tolerance and hepatopancreas histology of white shrimp Litopenaeus vannamei fed diets containing different carbohydrate sources at low salinity. (24th November 2014) - Wang, Xiaodan; Li, Erchao; Xu, Chang; Qin, Jian G.; Wang, Shifeng; Chen, Xuefen; Cai, Yan; Chen, Ke; Gan, Lei; Yu, Na; Du, Zhen‐Yu; Chen, Liqiao
Abstract: Juvenile Litopenaeus vannamei farmed at 3.0 psu were fed five diets containing glucose, sucrose, wheat starch, corn starch or potato starch as the carbohydrate (CBH) source. Shrimp were fed for 50 days to explore the effect of dietary CBH source on growth, body composition and ammonia tolerance. The specific growth rate of body length of shrimp fed glucose was the highest and significantly higher than those fed potato starch. The survival rate of shrimp fed glucose was 89.44%, and it was the highest and significantly higher than those fed wheat starch. Whole shrimp body crude protein and lipid of the corn starch group were 140.2 g kg −1 and 10.1 g kg −1 respectively. And they were significantly higher than those fed wheat starch. Shrimp fed potato starch had higher hepatopancreas and muscle glycogen. Shrimp fed sucrose had higher glucose‐6‐phosphate dehydrogenase and lower pyruvate kinase activities ( P < 0.05). Besides, shrimp fed starch produced more B cells in hepatopancreas tubules than those fed glucose or sucrose. Shrimp fed different sources of CBH differed in the number of R cells. After 96‐h of ammonia nitrogen challenge, the survival rate of the treatments from high to low in turn was glucose, wheat starch, corn starch, sucrose and potato starch, and no significant differences were observed among all treatments. Based on shrimp growth and the economic problems of practical production, we recommend wheat starch as CBH source in practical diets for L. vannamei farmed at low salinities.